Vertical Writing Connected (The Utility of Vertical Connected in Elementary School) - Zharifah, Jihan Inas; Pangesti, Prahasiwi Cahya; Andriani, Rahma Putri (Prosiding University Research Colloquium, 2021)
In Indonesia, the writing has developed. In the past, the writing was in italic and continuous form, but in 1983 the government issued a regulation regarding the standard form of writing. Writing in cursive with its unique form has many benefits, Cursive writing is an activity to form continuous writing. Writing cursive is the process of forming letters that are related to each other to form a word, on a flat plane using a writing utensil. Curved letters are one of the unique types of writing. In the international world, cursive writing is known as cursive writing.